Atención al cliente en el Agro Servicio “El Pueblo”, en la Parroquia Febres Cordero, periodo 2022. - Toapanta Olivo, Edwin Eddy (2023)
The ago service "El Pueblo" is an autonomous company located in Pueblo Nuevo, in the Febres Cordero parish. Its main activity is the commercialization of agricultural inputs at wholesale and retail in the area and its surroundings. During the period 2022, a study was carried out to evaluate the quality of customer service in this company. The analysis of customer service focused on various aspects, such as customer satisfaction, customer service efficiency, product availability and knowledge, staff friendliness and empathy, and problem solving. Data were collected through surveys, direct observations and analysis of customer interactions. The results show that customer service at the "El Pueblo" ago-service during 2022 was generally positive. Most clients expressed satisfaction with the attention received, highlighting the friendliness and willingness of the staff to help and provide information on agricultural products. However, areas for improvement were identified, such as waiting times in some cases and opportunities to expand staff knowledge about specific products. Based on these findings, recommendations are proposed to strengthen customer service, such as implementing periodic training for staff, strategies to reduce waiting times, and optimizing the availability of agricultural products. These suggestions are aimed at continuing to improve the customer experience at "El Pueblo" Airservices and strengthening its position in the agricultural inputs market in the area and surrounding areas. This summary is based on the information provided and aims to capture the key aspects of the study on customer service at "El Pueblo" Airservices during the year 2022. If there are more details or specifics you would like to add, feel free to let me know.